THIN FILMS OF ZnSe MODIFIED WITH Fe2+ AND Cu2+ FOR PHOTOELECTROCATALYSIS OF METHYL ORANGE WITH ACTIVE CHLORINE SPECIES - Ramírez Ubillús, Manuel Alejandro (2021)
Thin films of zinc selenide (ZnSe) modified with Fe2+ and Cu2+ ions were obtained by the electrodeposition method and were studied as catalysts in the photoelectrocatalysis process for the degradation of methyl orange with active species of chlorine. The characterization of the synthesized material indicated the presence of microparticles with a size of 0.5 μm. The X-ray diffractograms showed the (111) and (220) planes of ZnSe, as well as the (111) plane of FeSe. Likewise, the Raman spectra showed characteristic vibrations of ZnSe. The presence of Zn, Se and Cu were corroborated by the EDS technique, in a non-stoichiometric proportion. The ZnSe and ZnSe-Fe films showed absorption maxima close to 545 nm, while the ZnSe-Cu film showed an energy reduction up to 595 nm. The compound ZnSe showed a good electrocatalytic activity with total discoloration in 45 min, when introducing Fe2+ and Cu2+ ions, the discoloration time improved to 35 min for ZnSe-Fe and 25 min for ZnSe-Cu.